Statement of Tax Policy No. 3 Elimination of the Double Tax on Dividends: Statement of Tax Policy No. 4, Estate and Gift Tax Reform. - Huntington, Virginia R.; Dominiak, Gere (The Accounting Review, 1977)
Abstract Reviews two books on tax policy in the United States. 'Statement of Tax Policy No. 3, Elimination of the Double Tax on Dividends'; 'Statement of Tax Policy No. 4, Estate and Gift Tax Reform.'